Development and Validation of a Short-Version of the European Portuguese WHOQOL-OLD Scale - Gil, I.; Santos-Costa, P.; Bobrowicz-Campos, E.; Sousa, L.; Vilar, M.; Apóstolo, J. (Gerontechnology III. IWoG 2020. Lecture Notes in Bioengineering, 2021)
Background: Recognizing the importance of assessing quality of life in older adults, the World Health Organization introduced in 2006 the World Health Organization Quality of Life - Older Adults Module (WHOQOL-OLD) scale, which has been adapted to several international settings. Given the need to comprehensively assess older adults in this domain, without extending the duration of this process, international recommendations have emerged to develop shortened versions of the WHOQOL-OLD scale. Purpose: To develop and validate a short version of the European Portuguese WHOQOL-OLD for older adults who resort to geriatric care facilities. Methods: Psychometric validation study, conducted in two phases. Initially, the qualitative and quantitative analyses of WHOQOL-OLD general items and facets were performed to select the items with the highest content validity and to extract the experimental reduced version of the instrument. This experimental version, comprising 18 items, was tested in a sample of nursing home residents. Based on the Classical Test Theory item-total statistics, the most representative items were identified, and the 8-item version of the instrument was proposed. This 8-item WHOQOL-OLD was administrated to 125 participants recruited in geriatric care facilities. Results: The Item Response Theory-based analyses showed that the 8-item WHOQOL-OLD has satisfactory psychometric properties, with none of the items being a source of moderate/severe misfit or revealing a differential functioning. Conclusions: The 8-item WHOQOL-OLD constitutes an interesting alternative for the assessment of the quality of life in Portuguese seniors integrating geriatric care facilities. Future studies in populations of older adults with different sociodemographic and clinical profiles are warranted.